(3JbjjO aj Gdcfis
(3ChdgG (B:s
(3MQa GdCda (B: (3BOe , CHh GdHTQ , CHh GdJhHI s
(3BNQgG (B:s
(3MQa GdjGA jhfS (B: (3CHh GdfGI jhSa , CHh GdMLGL s
(3HgG fXGe GdJYbjHIs
(3JbjjO ai Gdcfi hgh Cf jCJi HGdGSe heG jWdb Ydjg ef Gdcfis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdCSJGP eMeO Gdefhfi HGdQHGW ef GdecJHGJ GdNGUI (B(30 / 653) s
Keywords: (3GdJGQjNs